Effects of Organizational Justice and Leader Behavior on Job Satisfaction with Demographic Characteristics As Control Variable - Haji Tirta; Ririn Handayani; Fahmi Oemar (Yayasan Education Al Aqsho Modern, 2022)
This study aims to see how the effects of organizational justice and leader behavior on job satisfaction with demographic characteristics as control variables. In addition, this study will also look at the interaction of these two variables and how organizational justice affects the performance of the Riau Province Tourism Office. This type of research is explanatory research. The population is employees at the Tourism Office of Riau Province, totaling 109 people. Data analysis in this study using SEM-PLS. Based on the data processing, it was found that women's job satisfaction was better than the job satisfaction of men in the Riau Province Tourism Office employees. In addition, the understanding of organizational justice has been proven to affect the job satisfaction of the employees of the Riau Province Tourism Office. The limitation of this study is the lack of population size used. So it is suggested to further researchers to conduct more in-depth research on organizational justice per indicator. In order to be able to explain more deeply on this variable so that the causes of job satisfaction will be clearer.